PECULIARITIES OF TEACHER- STUDENT INTERACTION IN E-LEARNING ENVIRONMENT - Spridzāns, Mārtiņš (Border Security and Management, 2018)
While implementing e-learning courses at the State Border Guard College of the Republic of Latvia, the author of this article has discovered several differences in communication between students compared to traditional learning. Since the e-learning is going to expand in the future it is essential to explore theoretical and practical concepts on teacher student interaction peculiarities in e-environment. The author has gathered suggestions and proposals on best practices of teacher student interaction in order to improve e-learning outcomes. The goal of the article is to explore the peculiarities of the interaction between teachers and students in e-learning environment and provide suggestions on improving the efficiency of teacher-student interaction in e-learning.